Biocolorants extracted from native Cerrado fruits applied in biodegradable packaging: A sustainable and natural alternative - Jaqueline Ferreira Silva; Carmen Torres Guedes; Eloize da Silva Alves; Suelen Siqueira dos Santos; Grasiele Scaramal Madrona; Diogo Francisco Rossoni; Mônica Regina da Silva Scapim (Ciência e Agrotecnologia, 2025)
ABSTRACT Biodegradable packaging has received considerable attention as a sustainable alternative. One way to increase its functionality is to incorporate bioactive compounds extracted from plants into polymeric matrices to create active packaging. Fruits from the Cerrado biome are rich sources of bioactive compounds, including antioxidants and antimicrobials, making them valuable for human health, functional foods, and active packaging development. In this study, we extracted and quantified total carotenoids from cerrado fruits (cagaita and mamacadela) using ultrasonic equipment with various time and temperature parameters. The extract with the highest carotenoid content was incorporated into biodegradable active packaging at concentrations of 20% and 30%. The mamacadela extract contained 12 times more total carotenoids than the cagaita extract, with values of 363.00 ±0.05 mg β-carotene/100 g and 30.00 ±0.03 mg β-carotene/100 g, respectively. The optimal extraction conditions (363.00 ±0.05 mg β-carotene/100 g) were achieved at 60 °C for 60 min in a conventional bath with agitation at 35 ±5 rpm. Incorporating the extract into the films resulted in a positive correlation between the extract concentration and increased stiffness, whereas the permeability of water vapor decreased. Compared to the control sample, the films containing the extract exhibited a noticeable color shift toward yellow. The developed films showed satisfactory mechanical properties, water vapor resistance, and enhanced coloration, making them a viable and sustainable option for active food packaging.